Analisis Regulasi dan Kebijakan Keamanan Hayati dan Peluang Keberhasilan Adopsi Benih Transgenik di Indonesia - Saragih, Edwin S; Sitorus, Santun RP; Harianto, Harianto; Moeljopawiro, Sugiono (Jurnal AgroBiogen, 2010)
Analysis of Regulation and Policy on Biosafety andLikelihood of Transgenic Seeds Adoption in Indonesia.Edwin S. Saragih, Santun R.P. Sitorus, Harianto, andSugiono Moeljopawiro. Since more than 10 years, anumber of works in field of modern biotechnology havebeen programmed in public research institutes anduniversities in Indonesia and few foreign companies haveput efforts in introducing transgenic varieties. This significantdevelopment raises intriguing question as to why there hasnot been any transgenic food crop seed planted by farmersin the country. A status quo was observed in whichregulatory regime on biosafety has been in a situation ofprolonged transitional phase and necessary institutionalframework has not been firmly in place. There weredistinguished lines among stakeholders on benefitawareness, risks perception and worry on multinationalcompanies’ control over seed supply. There is a fairexpectation that similar benefits experienced by adoptingcountries could also help increase food production inIndonesia. However, potential contribution of transgenicseeds for the country is still largely unexplored. There arenumbers of potential transgenic seeds namely transgenicrice, soybean, potato, tomato and corn, with the latter wouldshow slightly better likelihood of success once adoptionhappens. Decision making instrument as determinant factorin ensuring safe application and release of transgenic seedshas not yet existed despite the fact that capacity for biosafetyassessment conduct is undoubtedly sufficient. It is importantto note that the new regulation on biosafety (PP No. 21/2005)open opportunities for assessing transgenic product under atransitional clause. Nonetheless, the new regulation has notbeen able securing food safety statement of importedtransgenic products (especially corn and soybean) whichhave been used for domestic consumption.